SEJARAH PEMBANGUNAN PENJARA (JEIL) PENINGGALAN BELANDA DI KABUPATEN BENGKALIS - Jeniska, Bella; ', Prof. Dr. H. Isjoni, M.Si; ', Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Jail is one place where men be boxed in and drawn the line by itsfreedom. Penitentiary position don't despite one scene which happens at the momentColonial nation come to gain control Indonesia. On year 1883, Dutch Colonialgovernment, build one jail which is known by the name of Huis Behauring's Van (inDutch language) at Bengkalis's Regency. This jail is utilized to bate captive and rebelthat tries to drive out Dutch of Bengkalis's Regency area. This research intent (1 ) toknow how instructions E.H.Doorleben at Regency Bengkalis, (2 ) to know history bebuilt penitentiary at Bengkalis's Regency, (3 ) to know form and building part prisonDutch remainder at Regency Bengkalis, (4 ) to know life form prisoners at penitentiaryone built by Dutch at Regency Bengkalis. Method that is utilized in this research iskualitatif's observational method. Method kualitatif is a methodic that don't utilizenumber in data collecting and deep give interpretation to its result. Acquired data ofyielding interview then dianalisis in lingual alone. There is location even its researchwhich is at Bengkalis's Regency, correct it at Clears A Root Hero. Observational time tobe begun of proposal seminar until with Paper test. Data collecting tech that is utilizedwhich is interview tech, tech documents, studi's tech studi's library and techcomparability.Keywords: Jail, Bengkalis's regency